Global ocean spatial suitability for macroalgae offshore cultivation and sinking - Alevizos, Evangelos; Barillé, Laurent (Frontiers in Marine Science, 2023)
Macroalgae offshore cultivation and sinking is considered a potentially practical approach for ocean-based carbon dioxide removal. However, several considerations need to be resolved to assess the effectiveness and sustainability of this approach. Currently, several studies focus on the area required for climaterelevant carbon sequestration through macroalgae cultivation and sinking without considering realistic, global spatial limitations. This study uses a spatially-explicit suitability assessment model for optimised open-ocean afforestation and sinking site designation. By applying specific maritime, ecological and industrial constraints, two maps are produced: a) suitable areas for macroalgae offshore cultivation and sinking, and b) suitable areas for macroalgae sinking only (for sequestration purposes). These data provide a more realistic approach to quantifying the ocean surface (including the corresponding depths) required for macroalgae offshore cultivation and sinking within a spatially sustainable framework. The resulting maps estimate the respective suitability areas within the EEZs of the world countries. A total area suitable for macroalgae offshore cultivation and sinking is calculated at 10.8M km 2, whereas sinking-only areas account for 32.8M km 2 of the offshore ocean. The implications of spatial suitability patterns at global and national levels are discussed. We suggest that the concept of 'grow nearshore, sink offshore' should be explored as an alternative to offshore cultivation.